PENGARUH LINGKUNGAN SOSIAL, INOVASI, TEKNOLOGI DAN MODAL, TERHADAP MINAT BERBISNIS PADA MAHASISWA PROGRAM STUDI AKUNTANSI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS ISLAM MALANG - Redy Arbiansyah; Dwiyani Sudaryanti; Siti Aminah Anwar (Universitas Islam Malang, 2021)
This study aims to examine the effect of social environment, innovation, technology, and capital on business interest in students of the accounting study program, Faculty of Economics and Business, Islamic University of Malang. The population used in this study were all students majoring in accounting at the Islamic University of Malang. The sampling technique in this study used purposive sampling in order to obtain 85 research samples. The method of sampling is using a questionnaire (questionnaire). The data analysis method used is the model feasibility test (F test), determination test (R test), partial test (t test). From the results of this study, the independent variables of social environment, innovation, technology, and capital have a simultaneous and partial effect on the dependent variable of business interestKeywords: Business Interest, Technology, Social Environment, Capital, Social Media, Innovation